Contemporary Intellectual Property Issues Of Parallel Import In Russia - Maxim V. Mikhailov, Vyacheslav V. Zubenko (International Journal of Advanced Science and Technology, 2020)
IP rights protection deficiencies represent the risks that any international business would calculate before dealing with a Russian counterparty. Such a problematic issue as intellectual property rights exhaustion principle has been changing in Russia over time, affecting parallel importers and business with Russia in general. In its recent history, the Russian Federation has seen all three regimes on exhaustion of IP rights: international, regional, and national. Currently, in the contexts of sanctions and anti-sanctions, relatively young Russian intellectual property system is still looking for the balance between public interests and business support in terms of parallel import regulation. Therefore, the study aimed to make a detailed analysis of the contemporary problems of parallel import in Russia and the Eurasian Economic Union to find out the optimal approach to the regulation of this sphere. The study was conducted based on the application of general scientific methods of logical and comparative analysis, classification, systematization, grouping, and generalization, as well as prognostic methods. As a result, the authors concluded that in the face of serious socio-economic and financial losses, Russia’s compliance with TRIPS agreement obligations a priori implies an orientation towards supporting international business, as well as raising administrative and financial barriers for national legal entities. Other EAEU countries have faced a similar set of circumstances. In this regard, EAEU member countries have to proceed with the legislative development of principles and practices of applying the collective principle of exhaustion of rights. The best option seems to be to maintain the regional principle with the pointwise introduction of exceptions for the vital types of goods, in the production of which the Russian Federation has not yet reached a high share of independence from external technology suppliers.